2001
DOI: 10.1016/s0896-6273(01)00420-2
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Inheritance of Radial Glial Fibers by Cortical Neurons

Abstract: Recent studies demonstrated the neuronogenic role of radial glial cells (RGCs) in the rodent. To reveal the fate of radial glial processes, we intensively monitored divisions of RGCs in DiI-labeled slices from the embryonic day 14 mouse cortex. During RGC division, each pia-connected fiber becomes thin but is neither lost nor divided; it is inherited asymmetrically by one daughter cell. In divisions that produce a neuron and a progenitor, the neuron inherits the pial fiber, also grows a thick ventricular proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
721
4
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 822 publications
(770 citation statements)
references
References 54 publications
38
721
4
7
Order By: Relevance
“…At the onset of neurogenesis, most cell divisions in the VZ are asymmetric, with one daughter cell remaining in the VZ and the other cell exiting this zone to differentiate. Several imaging studies suggest that daughter cell fates may be regulated by the asymmetric inheritance of determinants associated with the apical membrane of the progenitor cell, such that the daughter cell that inherits this domain retains a progenitor cell fate [24][25][26][27]. At mid-to late stages of neurogenesis, the outcomes of VZ cell divisions undergo a fundamental alteration.…”
Section: Cellular Studies Of Cell Fate Determination Suggest a Progrementioning
confidence: 99%
“…At the onset of neurogenesis, most cell divisions in the VZ are asymmetric, with one daughter cell remaining in the VZ and the other cell exiting this zone to differentiate. Several imaging studies suggest that daughter cell fates may be regulated by the asymmetric inheritance of determinants associated with the apical membrane of the progenitor cell, such that the daughter cell that inherits this domain retains a progenitor cell fate [24][25][26][27]. At mid-to late stages of neurogenesis, the outcomes of VZ cell divisions undergo a fundamental alteration.…”
Section: Cellular Studies Of Cell Fate Determination Suggest a Progrementioning
confidence: 99%
“…Whole-cell patch-clamp recordings with single-cell dye labeling have revealed the morphology and measured the membrane properties of randomly chosen cells in contact with the ventricular surface, suggesting that cells with the characteristic morphological features of RG cells have the physiological features of precursor cells (LoTurco et al, 1991;Noctor et al, 2002). Similarly, the application of DiI or fluorescent microbeads to the pial surface of developing neocortex labels mitotically active VZ cells with distinct RG morphology (Malatesta et al, 2000;Miyata et al, 2001), and has demonstrated that these cells constitute more than 90% of mitotically active cells in the VZ (Noctor et al, 2002(Noctor et al, , 2004.…”
Section: Radial Glial Cellsmentioning
confidence: 99%
“…Through lineage studies using retroviruses in chick and rodent telencephalons, radial glia and neurons are suggested to be lineally related (Gray and Sanes, 1992;Halliday and Cepko, 1992), whereas solid studies have confirmed that rodent RG cells act as neural precursor cells (Malatesta et al, 2000;Miyata et al, 2001;Noctor et al, 2001Noctor et al, , 2004Tamamaki et al, 2001). The vast majority of dividing cells in the neocortical VZ, either in the S-phase or in the M-phase, express RG markers.…”
Section: Radial Glial Cellsmentioning
confidence: 99%
See 2 more Smart Citations